2021
DOI: 10.1037/tmb0000035
|View full text |Cite
|
Sign up to set email alerts
|

Objective, subjective, and accurate reporting of social media use: No evidence that daily social media use correlates with personality traits, motivational states, or well-being.

Abstract: There is a lively debate on the effects of social media use, shaped by self-reported measurements of social media use. However, selfreports have been shown to suffer from low accuracy compared to logged measures of social media use. Even though it is unclear how problematic that measurement error is for our inferences, many scholars call for the exclusive use of "objective" measures. But if measurement error is not systematic, self-reports will still be informative. In contrast, if there is systematic error, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 76 publications
2
29
2
Order By: Relevance
“…This study is limited in that data came from sample of first-year students from a single university. However, the sample size exceeded those utilized in previous studies (e.g., Johannes et al, 2021;Junco, 2013), and self-reported daily SM platform use patterns mapped onto national survey data from of 18-24-year-olds (Anderson & Jiang, 2018;Auxier & Anderson, 2021), suggesting that findings may generalize to young adults beyond the current sample. An additional limitation was related to the RescueTime software application used in this study not being compatible with iPhones.…”
Section: Limitations and Future Directionscontrasting
confidence: 58%
See 2 more Smart Citations
“…This study is limited in that data came from sample of first-year students from a single university. However, the sample size exceeded those utilized in previous studies (e.g., Johannes et al, 2021;Junco, 2013), and self-reported daily SM platform use patterns mapped onto national survey data from of 18-24-year-olds (Anderson & Jiang, 2018;Auxier & Anderson, 2021), suggesting that findings may generalize to young adults beyond the current sample. An additional limitation was related to the RescueTime software application used in this study not being compatible with iPhones.…”
Section: Limitations and Future Directionscontrasting
confidence: 58%
“…In recent years, several studies have revisited the issue of selfreport accuracy in the context of SM use, generally replicating two findings with larger samples: reporting inaccuracies are common, and they tend toward the direction of over-reporting (Ernala et al, 2020;Sewall et al, 2020). However, these studies still share substantial limitations with Junco (2013) including the assessment of SM time on a specific electronic device (iPhones; Sewall et al, 2020), a single platform (Facebook; Ernala, et al, 2020), or lumping time on multiple SM platforms together (i.e., total SM time, Johannes et al, 2021;Sewall et al, 2020).…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, for example, concerns have grown over lacking conceptualizations of "screen time" (e.g., Kaye et al, 2020), the exclusive focus on between-person effects (e.g., Beyens et al, 2020), and the over-pathologization of media use (e.g., Billieux et al, 2015). These concerns are intertwined with a number of methodological issues, such as the "accuracy crisis" stemming from observed discrepancies between self-reported and logged digital media use (e.g., Parry et al, 2021), and the null or negligible findings found in studies embracing behavioral data (e.g., Johannes et al, 2021) or alternative analytical choices (e.g., Orben & Przybylski, 2019). 2.…”
Section: Fundingmentioning
confidence: 99%
“…However, a recent metaanalysis revealed that self-reported measures typically correlate only modestly with digital trace measures of TSM 11 , so that their convergent validity has become a serious reason for concern. However, except for Sewall et al 12 and Johannes et al 13 , hardly any study has focused on the predictive validity of self-reported measures of TSM, which focuses on the degree to which selfreported TSM and digital trace measures yield comparable effects on certain outcome variables.…”
mentioning
confidence: 99%